4. Nomenclature and syntaxonomy of castellano-cantabrian Thymus mastigophorus communities - Molina Maruenda, Andrés; Izco, Jesús (Lazaroa, 1989)
Rivas Goday, Borja & Izco (Anales Inst. Bot. Cavanilles 26: 153 et seq. including table 2; 1970) described a Thymus mastigophorus association found on the «páramos» of Masa and La Brújula in the province of Burgos, Spain.